SPIRITUAL JOURNEYS - Podgorski, Frank`` R (Journal of Dharma, 1986)
One myth or metaphor which enchants our age is the paradigm of Spiritual Journey. Even the Second Vatican Council chose to explain the Church as a pilgrim Church in journey or in transit. This has proven useful for a Church constantly seeking to discover its hidden depths. Moreover, a variety of religious traditions also bear witness to a host of different spiritual voyages undertaken by many different peoples in a variety of cultures and time perceptions. With the hope of expanding our understanding of Spiritual Journey, Journal of Dharma has invited a number of scholars to reflect on a variety of spiritual journeys while paying special attention to the role of the spiritual guide or director.